Study of Flow Patterns of Water-ionic Liquid System in T-junctions using Computational Fluid Dynamics Simulations: Effect of Channel Geometry and Superficial Velocity - Arijit A. Ganguli (Chemical Engineering Transactions, 2023)
Recovery of mixed plastics using liquid-liquid extraction is an emerging area of research. Green solvents like ionic liquids (IL) and efficient techniques like microchannels for extraction have considerable potential in extraction of plastics to maximize both solvent and plastic recovery with microchannels. New flow patterns have been observed experimentally for flow of greener solvents in microchannels and no reports of Computational Fluid Dynamics (CFD) simulations for such patterns are reported in literature. In the present work, CFD simulations for water-IL system in rectangular microchannels for the experimental conditions reported in literature have been carried out for different operating conditions, geometric parameters and physical properties of liquids in contact with each other in a two phase flow. Qualitative predictions for slug, plug, parallel and throat-annular flos show good agreement with experimental results while rivulet flows could not be predicted. Predictions in drop flow showed considerable deviations from experimental observations. Quantitative predictions for plug lengths were analysed for the experimental conditions reported in the literature. The deviations of 7-8% have been reported as compared to experimental results. This study shows the capability of numerical simulations to predict different flow patterns and depicts the potential for carrying out simulations for dissolution of plastics in microchannels in f